Au-nanocrystals-decorated δ-MnO2 as an efficient catalytic cathode for high-performance Li–O2 batteries. Issue 21 (8th May 2015) - Liu, Shuangyu; Wang, Guoqing; Tu, Fangfang; Xie, Jian; Yang, Hui Ying; Zhang, Shichao; Zhu, Tiejun; Cao, Gaoshao; Zhao, Xinbing
Abstract : Porous Au/δ-MnO2 on graphene-coated Ni foam exhibited a superior catalytic effect for Li–O2 batteries with Au-induced directed Li2 O2 growth. Abstract : A Li–O2 battery works based on the reversible formation and decomposition of Li2 O2, which is insulating and highly reactive. Designing a catalytic cathode capable of controlling Li2 O2 growth recently became a challenge to overcome this barrier. In this work, we present a new design of catalytic cathode by growing porous Au/δ-MnO2 electrocatalyst directly on a conductive substrate. We found that Au/δ-MnO2 can catalyze the directed growth of Li2 O2 into a thin/small form, only inside porous δ-MnO2, and along the surface of δ-MnO2 sheets. We proposed the catalytic mechanism of Au/δ-MnO2, where Au plays a critical role in catalyzing the nucleation, crystallization and conformal growth of Li2 O2 on δ-MnO2 sheets. Li–O2 batteries with an Au/δ-MnO2 catalytic cathode showed excellent electrochemical performance due to this favorable Li2 O2 growth habit. The battery yielded a high capacity of 10 600 mA h g −1 with a low polarization of 0.91 V at 100 mA g −1 . Superior cycling stability could be achieved in both capacity-limited (500 mA h g −1, 165 times at 400 mA g −1 ) and unlimited ( ca . 3000 mA h g −1, 50 cycles at 800 mA g −1 ) modes.